Analisis Penggantian Fuse Cut Out (FCO) pada Jaringan Distribusi 20 KV di PT. PLN (PERSERO) UP3 Cikupa - Agustian, Dendi; Septiani, Melti; Romdoni, Sohip; Muslim, Aldi Bragi; Anzhari, Hafizh; Aribowo, Didik (Journal of Electrical Power Control and Automation (JEPCA), 2024)
This study aims to analyze the process of replacing Fuse Cut Out (FCO) on the 20 kV distribution network at PT. PLN (Persero) UP3 Cikupa to enhance the reliability of the electricity distribution system. Fuse Cut Out (FCO) is an essential protective device designed to prevent damage to electrical equipment from overcurrent or short-circuits. In the 20 kV distribution network, FCO often experiences reduced functionality due to aging and environmental conditions. This research evaluates the current condition of FCOs and implements precise and safe FCO replacement procedures. The method used is a descriptive qualitative approach, with data collected through literature review, interviews, field observations, and FCO performance testing. The research findings indicate that placing an arrester after the FCO provides additional protection for transformers, selecting fuse link ratings in accordance with transformer capacity is crucial for effective protection, and proper coordination of fault current interruption significantly improves system reliability. These findings are expected to assist PT. PLN (Persero) in optimizing FCO replacement procedures to reduce disruptions and extend the operational life of distribution equipment.